Integrated management of insect vectors of human and animal diseases. Developing genetic control - Bouyer, Jérémy (Perspective, 2015)
<span style="font-size: 10pt; font-family: Arial; font-style: normal;" data-sheets-value=""1":2,"2":"The evolution of insecticide resistance in insect vectors of human and animal diseases and the introduction of exotic vectors to new territories, in a context of tighter regulations on approved molecules, call for the development of new pest control methods. Among these new methods, genetic control shows promise, as demonstrated by the tsetse fly eradication project in Senegal. It nevertheless requires complementary studies combining public and private research. Moreover, it must be combined with other methods of pest control – chemical, physical and biological – within an integrated management framework. "" data-sheets-userformat=""2":585,"3":[null,0],"6":"1":["1":2,"2":0,"5":[null,2,0],"1":0,"2":0,"3":3,"1":1,"2":0,"4":1],"9":0,"12":0">Version française de l'article <span style="font-size: 10pt; font-family: Arial; font-style: normal;" data-sheets-value=""1":2,"2":"The evolution of insecticide resistance in insect vectors of human and animal diseases and the introduction of exotic vectors to new territories, in a context of tighter regulations on approved molecules, call for the development of new pest control methods. Among these new methods, genetic control shows promise, as demonstrated by the tsetse fly eradication project in Senegal. It nevertheless requires complementary studies combining public and private research. Moreover, it must be combined with other methods of pest control – chemical, physical and biological – within an integrated management framework. "" data-sheets-userformat=""2":585,"3":[null,0],"6":"1":["1":2,"2":0,"5":[null,2,0],"1":0,"2":0,"3":3,"1":1,"2":0,"4":1],"9":0,"12":0">The evolution of insecticide resistance in insect vectors of human and animal diseases and the introduction of exotic vectors to new territories, in a context of tighter regulations on approved molecules, call for the development of new pest control methods. Among these new methods, genetic control shows promise, as demonstrated by the tsetse fly eradication project in Senegal. It nevertheless requires complementary studies combining public and private research. Moreover, it must be combined with other methods of pest control – chemical, physical and biological – within an integrated management framework.